Cytotoxicity and toxicity evaluation of Xanthone Crude Extract on Hypoxic Human Hepatocellular Carcinoma and Zebrafish (Danio rerio) embryos - Shazrul Fazry; Muhammad Akram Mohd Noordin; Salahuddin Sanusi; Mahanem Mat Noor; Wan Mohd Aizat; Azwan Mat Lazim; Herryawan Ryadi Eziwar Dyari; Nur Hidayah Jamar; Juwairiah Remali; Babul Airianah Othman; Douglas Law; Nik Marzuki Sidik; et al. (MDPI, 2018)
Xanthone is an organic compound mostly found in mangosteen pericarp and widely known for its anti-proliferating effect on cancer cells. In this study, we evaluated the effects of xanthone crude extract (XCE) and α-mangostin (α-MG) on normoxic and hypoxic human hepatocellular carcinoma (HepG2) cells and their toxicity towards zebrafish embryos. XCE was isolated using a mixture of acetone and water (80:20) and verified via high performance liquid chromatography (HPLC). Both XCE and α-MG showed higher anti-proliferation effects on normoxic HepG2 cells compared to the control drug, 5-fluorouracil (IC50 = 50.23 ± 1.38, 8.39 ± 0.14, and 143.75 ± 15.31 μg/mL, respectively). In hypoxic conditions, HepG2 cells were two times less sensitive towards XCE compared to normoxic HepG2 cells (IC50 = 109.38 ± 1.80 μg/mL) and three times less sensitive when treated with >500 μg/mL 5-fluorouracil (5-FU). A similar trend was seen with the α-MG treatment on hypoxic HepG2 cells (IC50 = 10.11 ± 0.05 μg/mL) compared to normoxic HepG2 cells. However, at a concentration of 12.5 μg/mL, the α-MG treatment caused tail-bend deformities in surviving zebrafish embryos, while no malformation was observed when embryos were exposed to XCE and 5-FU treatments. Our study suggests that both XCE and α-MG are capable of inhibiting HepG2 cell proliferation during normoxic and hypoxic conditions, more effectively than 5-FU. However, XCE is the preferred option as no malformation was observed in surviving zebrafish embryos and it is more cost efficient than α-MG.